Ecological infrastructure and its role in sustainable urban development: analysis and perspectives - Ie. P. Tertytskyi (Вісник Харківського національного університету імені В.Н. Каразіна: Серія Екологія)
Purpose. To systematize and analyze contemporary scientific research and publications on the topic of ecological infrastructure in the context of sustainable urban development. The main goal is to define the concept of "Ecological Infrastructure" and its interrelation with the concept of sustainable development, as well as to identify key sustainable development goals that can be achieved through optimizing ecological infrastructure.